2015
DOI: 10.1124/jpet.115.225045
|View full text |Cite
|
Sign up to set email alerts
|

Marked Alteration of Rosuvastatin Pharmacokinetics in Healthy Chinese with ABCG2 34G>A and 421C>A Homozygote or Compound Heterozygote

Abstract: Rosuvastatin, a 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitor used to lower blood low-density lipoprotein cholesterol, is a substrate of the membrane ABCG2 exporter. ABCG2 variants have been shown to alter rosuvastatin disposition. The objective of this study is to determine the impact of ABCG2 34/421 compound haplotypes on rosuvastatin pharmacokinetics in healthy Chinese volunteer subjects. Eight hundred healthy Chinese males were genotyped by polymerase chain reaction-pyrosequencing for ABCG2 34G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 23 publications
4
40
0
Order By: Relevance
“…We believe that a trough concentration measured at a single time-point does not fully reflect the overall systemic exposure of rosuvastatin. Our speculation is supported by the previous reports that ABCG2 c.421C>A (rs2231142), a well-known polymorphism to increase the systemic exposure of rosuvastatin [16,20,21], does not alter the trough level of rosuvastatin. Of note, compared to the other volunteers, one volunteer of SLCO1B1 *17/*17 genotype exhibited a much higher trough level of 18.8 lg/mL.…”
Section: Discussionsupporting
confidence: 86%
“…We believe that a trough concentration measured at a single time-point does not fully reflect the overall systemic exposure of rosuvastatin. Our speculation is supported by the previous reports that ABCG2 c.421C>A (rs2231142), a well-known polymorphism to increase the systemic exposure of rosuvastatin [16,20,21], does not alter the trough level of rosuvastatin. Of note, compared to the other volunteers, one volunteer of SLCO1B1 *17/*17 genotype exhibited a much higher trough level of 18.8 lg/mL.…”
Section: Discussionsupporting
confidence: 86%
“…37,[56][57][58][59][60] Increases in AUC by~160% were also demonstrated with ABCG2 rs2231137 A variants (p<0.001). 56 However, ABCB1 polymorphisms were not associated with alteration of any pharmacokinetic parameters in patients taking rosuvastatin therapy. 90 OATPs facilitate hepatic uptake of rosuvastatin, and two different variants in SLCO1B1 (rs2306283 and rs4149056) were associated with rosuvastatin pharmacokinetics.…”
Section: Rosuvastatin Pharmacogenetics: Safetymentioning
confidence: 85%
“…Several studies have examined the effects of polymorphisms related to rosuvastatin pharmacokinetics; association between the ABCG2 rs2231142 A variant and changes in the pharmacokinetic parameters has been found . Increases in AUC by ~160% were also demonstrated with ABCG2 rs2231137 A variants (p<0.001) . However, ABCB1 polymorphisms were not associated with alteration of any pharmacokinetic parameters in patients taking rosuvastatin therapy .…”
Section: Rosuvastatinmentioning
confidence: 99%
“…When we digitally quantified the data presented in Fig.2a for AUC (0−t) in that paper 10 , median values for Chinese and Japanese were 62% and 35% higher, respectively, compared to Caucasians, versus the 11% difference we observed. In a recent study, Wan et al reported that ABCG2 c.34AA , with an allele frequency of 12.6% in Chinese, also has a significant effect on rosuvastatin pharmacokinetics in healthy Chinese subjects 25 , yielding a mean decrease of 34% in CL/F, although no change was observed for the heterozygous carrier of c.34GA. However, the volunteers here were not controlled for ABCG2 c.34 A>G SNP, since our clinical study preceded this publication.…”
Section: Discussionmentioning
confidence: 99%